Equações e inequações lineares: uma proposta para o Ensino Médio através de Problemas de Programação Linear e de um software livre - Pinho, Ana Paula Bueno de Camargo [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Este trabalho visa apresentar uma proposta para aplicar e aprofundar os conheci mentos sobre equações e inequações lineares no Ensino Médio, buscando contemplar as competências e habilidades específicas de Matemática e suas tecnologias, apontadas pela BNCC. Usando um software educacional livre da coleção Matemática Multimídia (pro duzido pela Unicamp), serão apresentadas situações que serão modeladas por equações e inequações, obtendo problemas de Programação Linear, que serão resolvidos pela análise de sua representação gráfica, através da inspeção dos vértices do conjunto viável para a solução.

This study aims to present a proposal to apply and improve the knowledge about linear equations and inequalities in High School, seeking to contemplate the specific competences and abilities of Mathematics and its technologies, pointed out by the BNCC. Using a free educational software from the Multimedia Mathematics collection (produced by Unicamp), situations will be presented that will be modeled by equations and inequalities, obtaining Linear Programming problems, which will be solved by analyzing their graphical representation, by inspecting the vertices of the viable set for the solution.
Linear equations and inequalities: a proposal for high school through of Linear Programming Problems and of free software
Keywords: Sistemas Lineares; Equações e Inequações Lineares; Programação Linear; Software Educacional; Linear systems; Linear equations and inequalities; Linear programming; Educational software